2018
DOI: 10.1007/s00453-018-0476-8
|View full text |Cite
|
Sign up to set email alerts
|

On Plane Constrained Bounded-Degree Spanners

Abstract: Let P be a finite set of points in the plane and S a set of non-crossing line segments with endpoints in P . The visibility graph of P with respect to S, denoted Vis(P, S), has vertex set P and an edge for each pair of vertices u, v in P for which no line segment of S properly intersects uv. We show that the constrained half-θ6-graph (which is identical to the constrained Delaunay graph whose empty visible region is an equilateral triangle) is a plane 2-spanner of Vis(P, S). We then show how to construct a pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 11 publications
(14 reference statements)
0
29
0
Order By: Relevance
“…Our aim is to route on the constrained half-Θ 6 -graph. This graph was shown to be a plane 2-spanner of Vis(P, S) [2]. The authors also showed a partial routing result (only between visible vertices) on this graph [3].…”
Section: Local Routing On the Visibility Graphmentioning
confidence: 82%
See 3 more Smart Citations
“…Our aim is to route on the constrained half-Θ 6 -graph. This graph was shown to be a plane 2-spanner of Vis(P, S) [2]. The authors also showed a partial routing result (only between visible vertices) on this graph [3].…”
Section: Local Routing On the Visibility Graphmentioning
confidence: 82%
“…Lemma 1 (Lemma 1 of [2]) Let u, v, and w be three arbitrary points in the plane such that uw and vw are visibility edges and w is not the endpoint of a constraint intersecting the interior of triangle uvw. Then there exists a convex chain of visibility edges from u to v in triangle uvw, such that the polygon defined by uw, wv and the convex chain does not contain any constraint or vertex of P .…”
Section: Local Routing On the Visibility Graphmentioning
confidence: 99%
See 2 more Smart Citations
“…Bose and Keil [7] showed that the Constrained Delaunay Triangulation is a 4π √ 3/9 ≈ 2.42-spanner of Vis(P, S). The constrained Delaunay graph where the empty convex shape is an equilateral triangle was shown to be a 2-spanner of Vis(P, S) [6]. We look at the constrained generalized Delaunay graph, where the empty convex shape can be any convex shape.…”
Section: Introductionmentioning
confidence: 99%